Clinical utility of contact heat evoked potentials (CHEPs) in a case of mentalis nerve lesion - Amparo Lugo; Ada Ferrer-Fuertes; Lilia Isabel Correa; Michela Campolo; Jordi Casanova-Molla; Josep Valls-Sole (Clinical Neurophysiology Practice, 2018)
Objective: Nociceptive evoked potentials are still infrequently used in electrodiagnostic studies of single patients. We report a case in which the results of contact heat evoked potentials (CHEPs) provided unique information for the diagnosis. Methods: After biopsy for a local cementoma, a 21-year-old woman presented with neuropathic pain in the distribution of her left mentalis nerve. A CT scan showed a well circumscribed lesion near the mentalis nerve groove. We examined brainstem reflexes and evoked potentials conveyed through the mentalis nerve. Results: Blink reflex responses recorded from the orbicularis oculi, jaw jerk and masseteric silent period recorded from the masseter muscles and long latency evoked potentials recorded from Cz to electrical stimulation of the mentalis nerve were all within normal values, with no differences between sides. However, CHEPs, recorded from Cz to thermoalgesic stimulation of the left mentalis area were decreased to approximately 1/3 their size in comparison to stimulation to the unaffected side. Conclusion: While the patient reported symptoms and had neuroimaging signs of mentalis neuropathy, the sole electrophysiological abnormality identified was that of CHEPs, which specifically test small, unmyelinated fibers. Significance: Nociceptive evoked potentials can provide unique information on damage of small nerve fibers in specific cases. Keywords: Contact heat evoked potentials, Facial pain, Brainstem reflexes, Small fiber neuropathy